1999
DOI: 10.1021/jp9923522
|View full text |Cite
|
Sign up to set email alerts
|

Pressure Effect on CH3 and C2H3 Cross-Radical Reactions

Abstract: The effect of pressure on the cross-radical reactions of vinyl and methyl radicals has been investigated. These radicals were produced by excimer laser photolysis of methyl vinyl ketone (CH 3 COC 2 H 3 ) at 193 nm. The reaction products were detected and analyzed using a sensitive gas chromatograph and mass spectrometer. The study covered a pressure range from about 0.28 kPa (2.1 Torr) to 27 kPa (200 Torr) at 298 K. The yield of propylene (C 3 H 6 ), the cross-combination product of methyl and vinyl radicals, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
42
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(50 citation statements)
references
References 30 publications
6
42
2
Order By: Relevance
“…The C 3 H 6 adduct can lead to C 3 H 5 + H formation, which means that adduct stabilization and bimolecular product formation compete. The results of Stoliarov et al (2000) and Fahr et al (1999) as a function of pressure lead to lower k 0 values than k 0,CH 3 + CH 3 →C 2 H 6 (T ). We estimate k 0,CH 3 + C 2 H 3 →C 3 H 6 (T ) = 0.1 × k 0,CH 3 + CH 3 →C 2 H 6 (T ).…”
Section: C17mentioning
confidence: 86%
See 1 more Smart Citation
“…The C 3 H 6 adduct can lead to C 3 H 5 + H formation, which means that adduct stabilization and bimolecular product formation compete. The results of Stoliarov et al (2000) and Fahr et al (1999) as a function of pressure lead to lower k 0 values than k 0,CH 3 + CH 3 →C 2 H 6 (T ). We estimate k 0,CH 3 + C 2 H 3 →C 3 H 6 (T ) = 0.1 × k 0,CH 3 + CH 3 →C 2 H 6 (T ).…”
Section: C17mentioning
confidence: 86%
“…There is no barrier on the singlet surface, leading to the C 3 H 6 adduct (Thorn et al 2000;Qu et al 2010), and this reaction has been studied experimentally by Fahr et al (1999), Thorn et al (2000) and Stoliarov et al (2000) between 1 and 200 Torr. The H atom abstraction reaction by CH 3 is likely to be a separate channel with a rate constant that has been measured on several previous occasions (Fahr et al 1999;Stoliarov et al 2000). The C 3 H 6 adduct can lead to C 3 H 5 + H formation, which means that adduct stabilization and bimolecular product formation compete.…”
Section: C17mentioning
confidence: 99%
“…Two product branching studies of this reaction have very recently been performed by Stoliarov et al [60] and Fahr et al [61]. Low-pressure studies (P ϭ 0.9 -3.7 Torr He) at T ϭ 310 K by Stoliarov et al [60] found that the combination-stabilization channel and the disproportionation channel dominated with average yields of ϳ42% and ϳ40%, respectively, and the combination-decomposition channel was the minor channel with ϳ18% average yield.…”
Section: Discussionmentioning
confidence: 99%
“…Low-pressure studies (P ϭ 0.9 -3.7 Torr He) at T ϭ 310 K by Stoliarov et al [60] found that the combination-stabilization channel and the disproportionation channel dominated with average yields of ϳ42% and ϳ40%, respectively, and the combination-decomposition channel was the minor channel with ϳ18% average yield. At T ϭ 298 K, Fahr et al [61] measured a 39% yield for the combinationstabilization channel at P ϭ 2.1 Torr He, which increased to ϳ78% at P ϭ 200 Torr He.…”
Section: Discussionmentioning
confidence: 99%
“…CH + C 3 H 4 → H + CH 2 CHC 2 H 4.2e-10 0 0 1.4 14 , Butler et al 1981, Daugey et al 2005, Goulay et al 2009, Loison & Bergeat 2009 12.! At low pressure (Fahr et al 1999, Stoliarov et al 2000, Hébrard et al 2013, Thorn et al 2000 → Rate constant in the 10-50K deduced from (Sabbah et al 2007), branching ratio mainly from (Savee et al 2012) (see also (Knyazev et al 1992, Cavallotti et al 2014, Leonori et al 2015 35.! 86.7 % de C 3 H x (supposed to be C 3 H 4 **) and 13.3% of CH x + C 2 H y (Angelova et al 2004a, Angelova et al 2004b.…”
Section: Review Of the Gas Phase Reactionsmentioning
confidence: 98%